2022
DOI: 10.3390/ijerph19159241
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Pain Syndrome Risk Associated with Squats: A Systematic Review

Abstract: Patellofemoral pain syndrome (PFPS) is highly prevalent; it can cause severe pain and evolve into progressive functional loss, leading to difficulties performing daily tasks such as climbing and descending stairs and squatting. This systematic review aimed to find evidence, in the literature, of squat movements that can cause or worsen PFPS. This work was based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, and its protocol was registered in PROSPERO (CRD420191287… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…At the affected knee the JRFs decreased in the AP direction, whereas at the contralateral knee increased, suggesting an overload of the patellofemoral joint, especially at the sit‐down phase of the squats. In a recent metanalysis, Pereira et al 47 reported that all squat exercises cause tension overload in the patellofemoral joint, especially with a knee flexion between 60° and 90°. In accordance with the literature, knee flexion of 60°–90° was observed between 15% and 75% of the movement in this study, and the JRFs at the patellofemoral joint increased from 1.3 × BW to 5.1 × BW (392% increase) at the normal state.…”
Section: Discussionmentioning
confidence: 99%
“…At the affected knee the JRFs decreased in the AP direction, whereas at the contralateral knee increased, suggesting an overload of the patellofemoral joint, especially at the sit‐down phase of the squats. In a recent metanalysis, Pereira et al 47 reported that all squat exercises cause tension overload in the patellofemoral joint, especially with a knee flexion between 60° and 90°. In accordance with the literature, knee flexion of 60°–90° was observed between 15% and 75% of the movement in this study, and the JRFs at the patellofemoral joint increased from 1.3 × BW to 5.1 × BW (392% increase) at the normal state.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows that people who are overweight are also prone to this type of knee disorder [ 38 , 39 ]. Runner’s knee causes pain in and around the kneecap when patients are active, or after sitting for a long time with the knees bent [ 40 , 41 , 42 ]. Patients may hear rubbing, grinding, or clicking sound of the kneecap when bending and straightening knees.…”
Section: Case Study and Performance Evaluationmentioning
confidence: 99%
“…Furthermore, it reduces the monitoring time because only one course of action is needed to collect the required readouts. Typical parameters and constraint values of the injuries are collected from references [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. Specifically, the blood circulation time, T C , is set to 60 s. The blood velocity, v ( t ), is set as a time-dependent random process in the range between 3 cm/s and 15 cm/s.…”
Section: Case Study and Performance Evaluationmentioning
confidence: 99%
“…Patellofemoral Pain Syndrome (PFPS) is one of the most commonly observed painful dysfunctions in the knee joint, primarily affecting adolescents and young adults, predominantly females [ 1 ]. Its prevalence in the global population varies between 22.7% and 28.9% [ 2 ], especially in individuals in the age range of 12 to 19 years [ 3 ]. In the national context, the available scientific literature on this topic is still limited, making it difficult to determine the exact prevalence of PFPS in the child and adolescent population in Brazil [ 4 ].…”
Section: Introductionmentioning
confidence: 99%